RETRACTED: New supplementary feeds for sterlet in industrial cultivation - Ponomareva Elena; Geraskin Peter; Kovaleva Angelika; Sorokina Marina; Aleksandrova Uliana; Rudoy Dmitry (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001